2012
DOI: 10.1016/j.atherosclerosis.2012.06.068
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal lipoprotein particles and cholesterol efflux capacity in patients with psoriasis

Abstract: Objectives Psoriasis is a Th-1/17 mediated inflammatory disease associated with increased risk of cardiovascular disease (CVD). Inflammation may modulate lipoprotein particle number and directly impair HDL functions, in particular reverse cholesterol transport (RCT). We sought to study how chronic in vivo inflammation modulates lipoprotein particle composition using nuclear magnetic resonance spectroscopy (NMR) and HDL efflux in psoriasis. Methods and Results We prospectively enrolled a consecutive sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
125
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 141 publications
(140 citation statements)
references
References 16 publications
11
125
1
3
Order By: Relevance
“…Analysis of the plasma lipid showed a decrease in total cholesterol, cholesterol esters, and phospholipids (Supplemental Figure 2B). We also measured serum cholesterol efflux capacity, which is the ability of HDL to accept lipids for reverse cholesterol transport; this has been shown to be impaired in psoriasis patients (20) and accelerate atherosclerosis in humans (21). We found HDL efflux to be significantly decreased by 20% in the K14-Rac1V12 -/+ mice (Supplemental Figure 2C).…”
Section: K14-rac1v12mentioning
confidence: 91%
“…Analysis of the plasma lipid showed a decrease in total cholesterol, cholesterol esters, and phospholipids (Supplemental Figure 2B). We also measured serum cholesterol efflux capacity, which is the ability of HDL to accept lipids for reverse cholesterol transport; this has been shown to be impaired in psoriasis patients (20) and accelerate atherosclerosis in humans (21). We found HDL efflux to be significantly decreased by 20% in the K14-Rac1V12 -/+ mice (Supplemental Figure 2C).…”
Section: K14-rac1v12mentioning
confidence: 91%
“…This is supported by the in vitro experiments demonstrating that rIL-22 downregulates ABCG1 expression in THP-1 macrophages and is functionally validated by reduced cholesterol effl ux. Mehta et al ( 49 ) recently reported on reduced cholesterol effl ux capacity of serum from patients with psoriasis. Although the IL-22 level was not reported in this cohort study, our data raises the hypothesis that elevated IL-22 levels often associated with autoimmune diseases, including psoriasis and rheumatoid arthritis, may mediate reduced cholesterol effl ux in foam cells.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of total cholesterol, triglycerides, lowdensity lipoprotein cholesterol, oxidatively modified lipids, and decreased levels of HDL(açılımını yaz) cholesterol is exhibited by patients with psoriasis by numerous studies (40,46). Mehta et also supportted that a more atherogenic lipoprotein profile and decreased HDL efflux capacity in psoriasis patients compared to controls beyond CVD risk factors.…”
Section: Dyslipidemiamentioning
confidence: 94%
“…Mehta et also supportted that a more atherogenic lipoprotein profile and decreased HDL efflux capacity in psoriasis patients compared to controls beyond CVD risk factors. The abnormal lipoprotein particle composition and HDL efflux capacity in psoriasis may provide a link between psoriasis and CVD (46). Lipoprotein (a) (Lp(a)) is a genetically established molecule whose function has been involved in cardiovascular pathology, and whose levels have been accounted to be raised in patients with psoriasis may be a factor contributing to an increased cardiovascular risk in patients with psoriasis (47).…”
Section: Dyslipidemiamentioning
confidence: 99%